Ankle–Brachial Index for the Assessment of Peripheral Arterial Disease in the Emergency Department. (January 2022) - Street, Tiffany K.
Abstract : Peripheral arterial disease, both acute and chronic ischemia, is a clinical diagnosis encountered in the emergency department setting. The emergency nurse practitioner should be able to recognize the clinical presentation, understand the diagnostic tools available to make an appropriate clinical diagnosis, and know how to coordinate the appropriate treatment plan with a vascular surgeon. Timely and appropriate diagnosis of limb-threatening arterial disease is imperative to restore arterial perfusion and prevent the loss of the lower extremity.